Photodesorption and electron trapping in n-type SnO2 thin films grown by dip-coating technique - Messias, Fábio R.; Scalvi, Luis Vicente de Andrade [UNESP]; Li, M. Siu; Santilli, C. V. [UNESP]; Pulcinelli, S. H. [UNESP] (Taylor & Francis, 1998)
Thin films of undoped and Sb-doped (2 atg%) SnO2 have been prepared by sol-gel dip-coating technique on borosilicate glasses. Variation of photoconductivity excitation with wavelength and optical absorption indicate indirect bandgap transition with energy of ≅ 3.5 eV. Conductance as function of temperature indicates two levels of capture with 39 and 81 meV as activation energies, which may be related to an Sb donor and oxygen vacancy respectively. Electron trapping by these levels are practically destroyed by UV photoexcitation (305 nm) and heating in vacuum to 200°C. Gas analysis using a mass spectrometer indicates an oxygen related level, which may not be desorbed in the simpler O2 form.
Keywords: Optical absorption; Oxygen vacancy; Photoconductivity; Tin dioxide; Traps; Wide gap semiconductor; Activation energy; Borosilicate glass; Coating techniques; Desorption; Electric conductance; Heating; Mass spectrometers; Semiconducting tin compounds; Semiconductor growth; Sol-gels; Thin films; Ultraviolet radiation; Electron trapping; Photodesorption; Sol-gel dip-coating techniques; Semiconducting films